Significant impact of cachexia index on the outcomes after hepatic resection for colorectal liver metastases. Issue 6 (11th May 2022) - Tanji, Yoshiaki; Furukawa, Kenei; Haruki, Koichiro; Taniai, Tomohiko; Onda, Shinji; Tsunematsu, Masashi; Shirai, Yoshihiro; Yanagaki, Mitsuru; Igarashi, Yosuke; Ikegami, Toru
Abstract: Introduction: The purpose of this study was to investigate the relation between preoperative cachexia index (CXI) and long‐term outcomes in patients with colorectal liver metastases (CRLM) after hepatic resection. Method: In all, 118 patients who underwent hepatic resection for CRLM were analyzed retrospectively. The relationship between CXI and the long‐term outcomes in patients after hepatic resection was investigated. CXI was calculated based on preoperative skeletal muscle index, serum albumin level, and neutrophil–lymphocyte ratio. Results: The multivariate analysis showed that extrahepatic lesion (hazard ratio [HR] 2.86, 95% confidence interval [CI] 1.48–5.53, P  < .01) and high CXI (HR 0.44, 95% CI 0.20–0.98, P  = .04) were independent and significant predictors of disease‐free survival. Moreover, extrahepatic lesion (HR 2.32, 95% CI 1.03–5.22, P  = .04), high CXI (HR 0.17, 95% CI 0.05–0.57, P  < .01), and curability R 1 or 2 (HR 3.29, 95% CI 1.23–8.78, P  = .02) were independent and significant predictors of overall survival. Conclusion: CXI is a useful prognostic factor for disease‐free survival and overall survival after hepatic resection in CRLM patients. Abstract : We investigate the relationship between preoperative CXI and long‐term outcome after hepatectomy in patients with colorectal liver metastases (CRLM), and this is the first report to show that CXI is a useful prognostic determinant after hepatectomy in patients with CRLM. #10;DFS and OS were predominantly prolonged in the group of patients with high CXI compared to the group of patients with low CXI.